Retrospective cohort study of elderly patients with acute appendicitis - Murat Arer, Ilker; Kus, Murat; Akkapulu, Nezih; Akdur, Aydincan; Avci, Tevfik; Sakulen Hargura, Abdirahman; Yabanoglu, Hakan (Annals of Medical Research, 2021)
None